Bladder Horn Appearance on Ultrasonographic Examination Prior to Cesarean Section: Does it Predict High Cranial Attachment of the Bladder? - İnci Kahyaoğlu; Fulya Kayıkçıoğlu; Serhan Kahyaoğlu; Sezin Ertürk Akasakal; Leyla Mollamahmutoğlu (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To investigate the value of bladder horn appearance seen on ultrasonography performed prior to cesarean section in prediction of high cranial attachment of bladder. STUDY DESIGN: The study was carried out in delivery unit of a teaching hospital. Two hundred pregnant women, 66 with and 134 without ultrasonographic appearance of bladder horn with at least one previous CS delivery beyond 37 weeks of gestation were enrolled in the study. RESULTS: The rate of high cranial attachment of the bladder in patients with or without bladder horn appearance is 33.3% and 26.9%, respectively (p=0.51). There was no difference in the incidence of dense adhesions between uterus and bladder requiring sharp dissection to create a bladder flap between two groups (22.7% vs. 20.2%) (p>0.05). CONCLUSION: Ultrasonographic appearance of horn shaped attachment of bladder base to the uterus does not predict the high attachment of bladder to the uterus.